A review of the genus Garra Hamilton 1822 of Bhutan, including the descriptions of two new species and three additional records (Cypriniformes: Cyprinidae) - Thoni, R.j.; Gurung, D.b.; Mayden, R.l. (Zootaxa, 2016)
Seven species of Garra are herein accounted for in Bhutan. Three new records of known species, G. arupi, G. birostris, and G. lissorhynchus, and two new species, G. bimaculacauda sp. nov. and G. parastenorhynchus sp. nov., are reported from central and southern Bhutan. Garra bimaculacauda sp. nov. is most notably different from its congeners by the presence of two dark spots on the lobes of the caudal fin, having one spot on each lobe. Meristic and morphometric differences from northeastern Indian congeners exist as well. Garra parastenorhynchus sp. nov. is differentiated from its congeners by the presence of a prominent, overhanging, club-shaped proboscis, and a suite of meristic and morphometric characters. Notes on the taxonomy are provided for some species. Notes are provided on the biology and ecology for most species, which have been inferred from field observations. Ranges are expanded for two recently described taxa from Northeast India G. arupi, and G. birostris. A key is provided to the currently known species of Garra within Bhutan.